Distribution Of Different Religion Legacy According To Islamic Instruction Law (Case Study Of The Supreme Court Decision Number 368 K/Ag/1995) - Sanjaya, Edy; Hastuti, Indira; Prasetyo, Budi (International Journal of Educational Research & Social Sciences, 2022)
The decision of the Supreme Court regarding the granting of wills to non-Muslim heirs is a breakthrough in relation to the inheritance of different religions. It is the consensus of scholars that religious differences (Muslims and non-Muslims) are one of the barrier factors for inheriting. With regard to religious differences, the mandatory will given by the Supreme Court is for non-Muslim siblings. The compulsory intention in KH1 is analogous to adopted children and adoptive parents. Religious differences are still barriers to inheriting each other by seeking a positive step by not limiting the understanding of inheritance law so far. This research method uses a normative juridical approach by reviewing various literature on granting wills to non-Muslim heirs. Data was collected through a literature study with relevant secondary legal materials sourced from statutory regulations, literature, both books, journal articles. Who are Muslim. It is the same with a Muslim who cannot inherit from a non-Muslim.